1991
DOI: 10.1159/000147082
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the Water-Clear Cell in the Parathyroid Gland of the Golden Hamster

Abstract: Water-clear cells and transitional forms between the chief cells and water-clear cells were observed in the parathyroid gland of the golden hamster. Their ultrastructure is described, and the origin of the water-clear cell is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1992
1992
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 5 publications
1
11
0
Order By: Relevance
“…It has been suggested that water-clear cells may be transformed from the chief cells and that the vacuoles may be dilated Golgi or RER cisternae or swollen mitochondria (Roth, 1970). In the parathyroid of the golden hamster, Emura et al (1991) observed ribosomes on the surface of some vacuoles and suggested that they may be derived from cisternae of the RER. In the present work, electron microscopy of human glands has provided some interesting data regarding the origin of the vacuoles; several forms, intermediate between secretory granules and the typical vacuoles, have been identified.…”
Section: Primary Hyperparathyroidismmentioning
confidence: 99%
“…It has been suggested that water-clear cells may be transformed from the chief cells and that the vacuoles may be dilated Golgi or RER cisternae or swollen mitochondria (Roth, 1970). In the parathyroid of the golden hamster, Emura et al (1991) observed ribosomes on the surface of some vacuoles and suggested that they may be derived from cisternae of the RER. In the present work, electron microscopy of human glands has provided some interesting data regarding the origin of the vacuoles; several forms, intermediate between secretory granules and the typical vacuoles, have been identified.…”
Section: Primary Hyperparathyroidismmentioning
confidence: 99%
“…Our previous reports have demonstrated that the water-clear cell was occasionally observed in the parathyroid glands of golden hamsters of different ages (Emura et al, , 1991. In the water-clear cell which was occasionally observed in the parathyroid glands of the control adult ( Fig.…”
Section: Resultsmentioning
confidence: 71%
“…It has been demonstrated that the water-clear cell was absent in normal human (Altenahr, 1981;Isono et al, 1990) or other vertebrate parathyroid glands . However, Emura et al (1990Emura et al ( , 1991 indicated that water-clear cells were observed in the parathyroid glands of golden hamster.…”
Section: Starvationmentioning
confidence: 99%
“…They derive from chief cells and may be capable of PTH secretion. Water-clear cells have been found in immersion-fixed PT glands of golden hamsters (Emura et al, 1991). They also occur in rabbit PT glands fixed by immersion (Fig.…”
Section: Development Of Other Cell Typesmentioning
confidence: 76%